Respon Pertumbuhan Tomat Cherry (Solanum lycopersicum var. cerasiforme) terhadap Konsentrasi Salinitas NaCl - Ambar Pratiwi; Elis Wahyu Krisjayanti; Inggita Utami (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2021)
Cherry tomato is a popular horticultural crop in Indonesia. The need for cherry tomatoes is starting to increase and they are starting to be consumed fresh as fruit or in processed form. The growth and productivity of cherry tomatoes is strongly influenced by the salinity of the growing media. Soil is classified as saline if the saturated extract from saline soil has a DHL or EC value of more than 4 dS/m. The aim of the study was to determine the growth response and the best NaCl concentration on growth, vitamin C content, and total phenol in cherry tomatoes. This research was conducted from March to May 2020 at the Green House of the University of Sarjanawiyata Tamansiswa. Cherry tomatoes were grown in a planting medium in the form of yard soil and manure with a ratio of 2:1, given a solution with various concentrations of NaCl every day to produce the effect of salinity of NaCl. The treatments given during data observation included growth, vitamin C content, and total flavonoids. The data obtained were analyzed using ANOVA, if there was a significant difference, then proceed with DMRT. The results of the analysis showed that several growth parameters gave significant differences, namely: plant height, compound leaves, and stem diameter. While the growth parameters that do not provide a significant difference in the number of flowers and the number of fruit. The highest vitamin C content in cherry tomatoes was obtained in the 1000 ppm treatment, amounting to 30.30 mg/ 100 g. The highest total phenol content of cherry tomatoes was found in the 1000 ppm treatment, amounting to 24.89 mg/ 100 g. The conclusion of this research is that the best NaCl concentration treatment is 1,000 ppm, where there are significant differences in plant height, compound leaves, and stem diameter. The concentration of 1,000 ppm also increased the highest total vitamin C and phenol content.